Efectos adversos y factores sociodemográficos para la no adherencia terapéutica al tratamiento con metotrexato en pacientes con artritis reumatoide - Cangas Ramírez, Mauricio José (Machala : Universidad Técnica de Machala, 2022)
Introduction: Rheumatoid arthritis is a disease of autoimmune origin that affects many people around the world, since there is no cure, there are medications that help improve the quality of life of the patient but that in turn cause adverse effects throughout the course of the disease. of your treatment,one of the cornerstones of treatment is methotrexate, which has been shown to be effective in relieving inflammatory symptoms and can be combined with biological drugs or corticosteroids depending on the criteria of the treating physician.Objective: To determine the adverse effects and sociodemographic factors that affect non-adherence to treatment with methotrexate, through a bibliographic review of scientific articles on the subject, for the education of patients with rheumatoid arthritis.Methodology: This descriptive bibliographical research was carried out qualitatively.Conclusion: The authors of the articles describe methotrexate as a drug that has several adverse reactions if there is not a correct use of it, either by combining it with folic acid or a greater consumption than necessary by the patient, that is why the correct adherence of the patient is of great importance,In addition, most emphasize that methotrexate is the cornerstone of treatment, whether combined with biological drugs or corticosteroids.
Introducción: La artritis reumatoide es una enfermedad de origen autoinmune que afecta a muchas personas alrededor del mundo, al no tener una cura existen medicamentos que ayudan a una mejora de la calidad de vida del paciente pero que a su vez ocasionan efectos adversos a lo largo de su tratamiento , una de las piedras angulares del tratamiento es el metotrexato el cual está demostrado que es eficaz para el alivio de los síntomas inflamatorios y se lo puede combinar con fármacos biológicos o corticoides dependiendo el criterio del médico tratante.Objetivo:Determinar los efectos adversos y los factores sociodemográficos que inciden en la no adherencia terapéutica al tratamiento con metotrexato, mediante revisión bibliográfica de artículos científicos referentes al tema, para la educación al paciente con artritis reumatoide.Metodología: Esta investigación bibliográfica de tipo descriptivo se realizó de manera cualitativa. Conclusión: Los autores de los artículos describen al metotrexato como un fármaco que tiene varias reacciones adversas si no existe un correcto uso del mismo ya sea combinándolo con ácido fólico o un consumo mayor al necesario por parte del paciente es por eso que la correcta adherencia del paciente es de mucha importancia, además la mayoría recalca que el metotrexato es la piedra angular del tratamiento ya sea para combinarlo con fármacos biológicos o con corticoides.
Keywords: ARTRITIS REUMATOIDE; ADHERENCIA; METOTREXATO